2011
DOI: 10.1152/physiolgenomics.00243.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression variation between African Americans and whites is associated with coronary artery calcification: the multiethnic study of atherosclerosis

Abstract: Coronary artery calcium (CAC) is a strong indicator of total atherosclerosis burden. Epidemiological data have shown substantial differences in CAC prevalence and severity between African Americans and whites. However, little is known about the molecular mechanisms underlying initiation and progression of CAC. Microarray gene expression profiling of peripheral blood leucocytes was performed from 119 healthy women aged 50 yr or above in the Multi-Ethnic Study of Atherosclerosis cohort; 48 women had CAC score >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 44 publications
2
34
0
2
Order By: Relevance
“…Alternatively, there may be a direct correlation between gene expression in circulating leukocytes that participate in the pathogenesis of arteriosclerosis. In agreement with this, previous microarray data from Huang et al [48] have identified the differential expression of several genes in circulating cells, including calcium- and bone-related genes, in individuals with and without vascular calcification.…”
Section: Genetics Of Arterial Stiffnesssupporting
confidence: 81%
“…Alternatively, there may be a direct correlation between gene expression in circulating leukocytes that participate in the pathogenesis of arteriosclerosis. In agreement with this, previous microarray data from Huang et al [48] have identified the differential expression of several genes in circulating cells, including calcium- and bone-related genes, in individuals with and without vascular calcification.…”
Section: Genetics Of Arterial Stiffnesssupporting
confidence: 81%
“…45 There may be inherent genetic predisposition for coronary calcification in blacks and whites, which remains to be determined. Huang et al 46 showed that race-related genes, such as GAB2, which is expressed at a lower level in blacks and also in those with low calcification may be another explanation for the lower prevalence of calcification in blacks. Furthermore, it has been reported that soluble epoxide hydroxylase gene polymorphism is associated with coronary calcification in blacks, but not in whites.…”
Section: Determinants Of Calcification - Gender and Race Differences mentioning
confidence: 99%
“…Additional studies are needed to better understand how the respective potential genetic loci and environmental factors entailed in family history and race/ethnicity interact with one another and how these affect clinically relevant endpoints. In this regard, one study has examined whole-blood gene expression profiles and CAC levels among white and African American women selected from MESA participants [49]. The study found concordantly decreased expression profiles of several genes in African Americans, particularly those involved in immunologic and inflammatory pathways, when compared to the overall multi-racial low CAC score group.…”
Section: Discussionmentioning
confidence: 99%